I found following statment to be true If the company has no debt outstanding, then its degree of total leverage equals its degree of operating leverage. Here is formula for DFL DFL = % change in EPS/ % change in EBIT How is the following formula is derived? DFL = % change in EPS/ % change in EBIT = EBIT/(EBIT - I) Here is the solution given for the proof for the statement. If debt = 0 then DFL = 1 because DFL = EBIT/(EBIT - I) If debt = 0 then I = 0 and DFL = EBIT/(EBIT - 0) = EBIT/EBIT = 1 DTL = (DOL)(DFL) If DFL = 1 then DTL = (DOL)(1) which complies to DTL = DOL